Pembelajaran Berbasis Masalah sebagai Solusi untuk Meningkatkan Minat dan Hasil Belajar Teks Prosedur melalui Integrasi Materi Kejuruan - Himayati, Baiq Reni Ardiyani; Mohzana, Mohzana; Murcahyanto, Hary (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to determine the impact of integrating vocational materials on students' interest and learning outcomes in procedural texts through the Problem-Based Learning (PBL) method in eleventh-grade mechanical engineering students at a vocational high school (SMK). The technique used was a quasi-experimental design with a non-equivalent control group design. The results showed that vocational material integration significantly increased student interest and learning outcomes. The experimental group showed a greater increase in interest, as indicated by better motivation, engagement, and self-confidence. Furthermore, students in the experimental group also improved their learning outcomes for procedural texts, as evidenced by improved test scores and learning completion. The conclusion is that integrating vocational material through PBL is efficacious in improving the quality of English instruction in vocational high schools. Keywords:Vocational Material Integration, Problem-Based Learning, Procedural Text